Exploring the origins of crystallisation kinetics in hierarchical materials using in situ X-ray diffraction and pair distribution function analysis. Issue 34 (25th March 2020) - Potter, Matthew E.; Light, Mark E.; Irving, Daniel J. M.; Oakley, Alice E.; Chapman, Stephanie; Chater, Philip; Cutts, Geoff; Watts, Andrew; Wharmby, Michael; Vandegehuchte, Bart D.; Schreiber, Moritz W.; Raja, Robert
Abstract : Novel  in situ  synchrotron total scattering measurements probe the assembly of primary building units into templated hierarchically porous aluminophosphate catalysts, providing unique insights to understanding crystallisation kinetics. Abstract : The discovery of novel catalytic materials is predicated on understanding contemporary synthetic processes. With this fundamental knowledge in place it becomes possible to modify the final material with subtle changes to the synthesis process. In this vein, hierarchical materials, formed by the addition of a mesoporogen within the hydrothermal synthesis, have attracted a significant amount of attention due to their catalytic benefits over analogous microporous species. In this work we monitor the hydrothermal synthesis in situ of a hierarchical and a microporous aluminophosphate, for the first time, combining total scattering and pairwise distribution function data. In doing so we observe the local formation of the species, and the longer range crystallisation processes concurrently.